# How do you simplify #5sqrt(9a^3)-6asqrta#?

By signing up, you agree to our Terms of Service and Privacy Policy

To simplify the expression 5√(9a^3) - 6a√a, we can break it down as follows:

First, simplify the square root of 9a^3: √(9a^3) = √(9) * √(a^3) = 3√(a^2 * a) = 3a√a

Next, substitute this simplified value back into the original expression: 5√(9a^3) - 6a√a = 5(3a√a) - 6a√a = 15a√a - 6a√a = (15a - 6a)√a = 9a√a

Therefore, the simplified expression is 9a√a.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7